2011
DOI: 10.1007/s11104-011-0937-1
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum resistance mechanisms in oat (Avena sativa L.)

Abstract: Background and aims Enhanced aluminum (Al) resistance has been observed in dicots over-expressing enzymes involved in organic acid synthesis; however, this approach for improving Al resistance has not been investigated in monocots. Among the cereals, oat (Avena sativa L.) is considered to be Al resistant, but the basis of resistance is not known. Methods A hydroponic assay and hematoxylin staining for Al accumulation in roots were used to evaluate Al resistance in 15 oat cultivars. Malate and citrate release f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
3
4
0
4
Order By: Relevance
“…Possible Al detoxification mechanisms may include: (1) selective permeability of the plasmatic membrane to reduce Al uptake (Archambault et al 1997), (2) proteins that are connected to Al secretion (Basu et al 1999), (3) -Xin et al 2009;Pellet et al 1996;Zheng et al 2005), (4) secretion of phenolic compounds (Ofei-manu et al 2001), and (5) organic acids (Liu et al 2009), which chelate Al ions. Initially, citrate was considered the main organic acid exudate for Al tolerance (Zheng et al 1998) by A. sativa roots; however, recent studies have shown only malate to increase its secretion in response to Al (Radmer et al 2012). Our data showing malate exudation by Al in roots of UFRGS 17 and not UFRGS 930598-6 roots support this recent work.…”
Section: Discussionsupporting
confidence: 83%
“…Possible Al detoxification mechanisms may include: (1) selective permeability of the plasmatic membrane to reduce Al uptake (Archambault et al 1997), (2) proteins that are connected to Al secretion (Basu et al 1999), (3) -Xin et al 2009;Pellet et al 1996;Zheng et al 2005), (4) secretion of phenolic compounds (Ofei-manu et al 2001), and (5) organic acids (Liu et al 2009), which chelate Al ions. Initially, citrate was considered the main organic acid exudate for Al tolerance (Zheng et al 1998) by A. sativa roots; however, recent studies have shown only malate to increase its secretion in response to Al (Radmer et al 2012). Our data showing malate exudation by Al in roots of UFRGS 17 and not UFRGS 930598-6 roots support this recent work.…”
Section: Discussionsupporting
confidence: 83%
“…URSCharrua e URSGuapa foram superiores ao controle tolerante UFRGS17 (Figura 2), ambas as cultivares não apresentaram indivíduos com recrescimento inferior a 15mm (Figura 1C e 1E) (CASTILHOS et al, 2011). É possível que a entrada de Al 3+ seja restringida pela secreção de ácidos orgânicos, como observado em variedades cultivadas nos Estados Unidos (RADMER et al, 2012). Em trigo, acredita-se que a tolerância depende do gene TaALMT1, que codifi ca um transportador de malato, e que o grau de tolerância dos genótipos está relacionado à expressão desse gene (DELHAIZE et al, 2012).…”
Section: Resultsunclassified
“…Essa inibição causa um sistema radicular defi ciente, acarretando insufi ciente absorção de água e infl uxo de íons para o desenvolvimento adequado da planta e diminuindo a sua produtividade (MA & FURUKAWA, 2003;PANDA et al, 2009 (SANCHEZ-CHACON et al, 2000;RADMER et al, 2012). Os mecanismos genéticos, fi siológicos e moleculares da tolerância ao Al 3+ em aveia ainda não estão totalmente elucidados.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…No entanto, globalmente, poucos cultivares são caracterizados quanto à sua resposta ao estresse por esse elemento, limitando o conhecimento sobre diferenças comportamentais entre diferentes constituições genéticas (Radmer et al, 2012).…”
Section: Introductionunclassified